INVESTIGASI PENYEBAB PENGEBOMAN IKAN DI PERAIRAN TELUK SALEH BERDASARKAN PERSEPSI DAN PRINSIP NELAYAN TERHADAP DESTRUCTIVE FISHING - Kautsari, Neri; Diahpebila, Tasya Ayu; Mardhia, Dwi; Iskandar, Syaifuddin; Bahri, Syamsul (Jurnal Sumberdaya Akuatik Indopasifik, 2024)
Fishing with explosives (fish bombs) is one of the cases of destructive fishing that occurs every year on the coast of Saleh Bay, Sumbawa, West Nusa Tenggara. The government has implemented several strategies to reduce destructive fishing, but these cases still occur on the coast of Saleh Bay. This research aims to determine fishermen's perceptions and principles regarding fishing using bombs. This research was conducted from June to August 2023 in Prajak Hamlet, Batu Bangka Village, Sumbawa, West Nusa Tenggara (NTB). The method used in this research is a survey. The survey was conducted through in-depth interviews with respondents. The number of respondents in this study was 50 people. Data were analyzed using descriptive analysis. Data is displayed with graphs. The research results show that there are still 2% of fishermen who think that bombs are a cheap fishing tool, produce abundant fish and are easy to operate. There were 2% of respondents who stated that there was nothing wrong with using bombs. The act of bombing fish was imitated by previous people. As many as 4% of fishermen are not sure that their actions will have an impact on the ocean. The majority of fishermen (72%) have a high level of confidence in using fishing gear recommended by the government, but there are 8% who feel unsure about using fishing gear recommended by the government. The results of this research indicate that there is still potential for fish bombing in the waters of Saleh Bay. Therefore, outreach activities are needed for fishermen regarding the impacts of using fish bombs.